2016
DOI: 10.1039/c6ce01800a
|View full text |Cite
|
Sign up to set email alerts
|

Ring size effect on the solid state assembly of propargyl substituted hexa- and octacyclic peptoids

Abstract: The investigation of the solid state assembly of propargyl substituted hexa- and octacyclic peptoids highlights the effect of ring size in determining the packing arrangement of the macrocycles. A layered arrangement is obtained in the case of the hexacyclic peptoid 1 and a tubular arrangement in the case of the octacyclic peptoid 2. Guest molecules either intercalate between the layers as in 1 or are located within the peptoid nanotubes as in 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…An analysis of the ϕ and ψ angles present in published peptoid structures (41 crystal structures, 5 NMR structures, 132 total dihedral combinations, Supporting Information Table S1) reveal that trans‐ and cis ‐amides show similar preferences for ϕ and ψ combinations, with trans ‐amide and cis ‐amide residues primarily occupying two main regions that span across the bottom and top edges of the Ramachandran plot (ϕ 70° and −70° and ψ 180° and −180°, Figure ). Replotting these data to represent ϕ and ψ from 0° to 360° (adding 360° to ϕ and ψ values below 0°, Figure C,F) shows that the preferred dihedrals lay in the same low‐energy regions for trans and cis disarcosine calculatations, with regions centered around (70°, 180°) and (290°,180°) (Figure C,F).…”
Section: The Ramachandran Plotmentioning
confidence: 99%
“…An analysis of the ϕ and ψ angles present in published peptoid structures (41 crystal structures, 5 NMR structures, 132 total dihedral combinations, Supporting Information Table S1) reveal that trans‐ and cis ‐amides show similar preferences for ϕ and ψ combinations, with trans ‐amide and cis ‐amide residues primarily occupying two main regions that span across the bottom and top edges of the Ramachandran plot (ϕ 70° and −70° and ψ 180° and −180°, Figure ). Replotting these data to represent ϕ and ψ from 0° to 360° (adding 360° to ϕ and ψ values below 0°, Figure C,F) shows that the preferred dihedrals lay in the same low‐energy regions for trans and cis disarcosine calculatations, with regions centered around (70°, 180°) and (290°,180°) (Figure C,F).…”
Section: The Ramachandran Plotmentioning
confidence: 99%
“…Izzo and coworkers studied the crystal structures of hexameric and octameric propargylated cyclic polypeptoids, that is, cyclo‐(Npa) 6 and cyclo‐(Npa) 8 , and the impact of ring size on the crystallization of cyclic polypeptoids with guest molecules . For cyclo‐(Npa) 6 , the guest molecules such as acetonitrile, water and DMSO molecules intercalate between layered crystal structure.…”
Section: Crystallization and Self‐assembly Of Polypeptoid Polymersmentioning
confidence: 99%
“…This molecular assembly represents the peptoid counterpart of -sheet secondary structures in proteins. It can be related to a general feature of the solid-state assembly of cyclic peptoids: CH 2 groups in peptoids replace NH groups in peptides to form backbone-to-backbone hydrogen bonds (Tedesco et al, 2014(Tedesco et al, , 2016Meli et al, 2016).…”
Section: Figure 14mentioning
confidence: 99%
“…We also concluded that methoxyethyl and propargyl side chains are the most effective in inducing a columnar arrangement of peptoid macrocycles. In fact, they act as pillars and extend vertically with respect to the macrocycle plane interacting with the backbone atoms of the macrocycles below and above (Maulucci et al, 2008;Izzo et al, 2013;Meli et al, 2016;Tedesco et al, 2016).…”
Section: Introductionmentioning
confidence: 99%